Impact of Danish Livestock and Manure Management Regulations on Nitrogen Pollution, Crop Production, and Economy - Sommer, Sven G.; Knudsen, Leif (Frontiers in Sustainability, 2021)
Reduction of nitrate (NO3) and ammonia (NH3) emission to the environment has since the 1980’ies been targeted by Danish environmental friendly regulations, which comply with regulation set by the European Union. Nitrate pollution of aquifers and surface waters caused by farming was observed in the start 1980’ies, and in the mid 1980’ies NH3 emission was known to contribute reactive nitrogen (N) to the environment. This article presents an overview and discussion of the effect of the initiatives and regulation aiming at reducing emission or losses of plant nutrient and their effect on farmer’s economy. The first initiatives was voluntary and the Environmental Agency and farmer organisation launched a “good agricultural practise” program aiming at reducing N loss by increasing N use efficiency and reducing N import. This was not efficient and was in the late 1980’ies followed up by regulations on how to manage manure and mineral fertilisers, which included a limitation of the number of animals per hectare agricultural land (Harmony rules). Nitrate leaching has been reduced with 45% mainly by restricting manure application to the period where the crop has a demand for plant nutrients and make it compulsory to grow crops that take up N during most of a year (grass, beets, catch crop, under sown grass). A high number of demonstration trials with animal manure combined with better slurry application technologies contribute to that farmers trust the measured N-use efficiencies and reduced over fertilization. In addition the government have forced the farmers to apply N below maximum N fertilizer rates (fertilizer and manure). Regulation has resulted in a 51% reduction in NH3 emission from livestock buildings, manure stores and manure application. In the years from 1994 to 2021 the regulation increased the requirement for utilization of animal manure, and in 2020/21 this is 75 percent of N in cattle- and 80 percent for pig slurry. Mineral N application to crops was by law 10-20 % below economical optimum from 1999to 2016. From 2016 the suboptimal N-quotas was replaced by higher requirements for catch crops. T